BaBao Dan Suppresses Tumor Growth of Pancreatic Cancer Through Modulating Transcriptional Reprogramming of Cancer-Related Genes - Song, Libin; Fang, Zhixiao; Pan, Chuanfang; Chen, Xiangyuan; Qian, Xiang; Cai, Yunyun; Zhang, Xiumei; Liu, Luming (Frontiers in Oncology, 2020)
Background & Aims: Pancreatic ductal adenocarcinoma (PDAC) is one of refractory malignancies without efficient therapeutics. Babo Dan (BBD) were partially effective to suppress tumor growth of PDAC in clinical practice. However, the possible molecular mechanisms were unclear. Methods: We established PDAC mice models and treated them with BBD through intragastric administration. Treated and control groups were then subjected to high-throughput RNA sequencing. We presented the transcriptional changes upon BBD treatment by using computational analysis comparing BBD-treated and control groups. Functional enrichment analysis were employed to investigate the biological processes or pathways that BBD modulates. Results: BBD treatment showed strong suppression on tumor growth of PDAC, even stronger than Gemcitabine. Through differential analysis comparing BBD-treated and control groups, we identified 638 up-regulated and 259 down-regulated genes in BBD-treated group. BBD was found to activate tumor suppressor genes, such as MTUS1, PDGFB, SOD3, and UCHL1. Furthermore, we revealed that BBD treatment inhibited cancer-related pathways and elevated activities of metabolism-related processes. The BBD-modulated metabolic genes were further showed to be associated with patient survival in an independent cohort with pancreatic cancer. Conclusion: BBD treatment modulated expression of cancer-related genes in PDAC. BBD suppresses cancer-related pathways and activated metabolic processes in PDAC. Our study suggest BBD treatment a potential effective therapeutics for patients with pancreatic cancer.